Controlled synthesis and near-infrared upconversion properties of 3D self-assembled NdVO4 microcrystals. Issue 12 (15th August 2019) - Lei, Tiyi; Li, Yuemei; Zheng, Wei; Dong, Jun; Wang, Rui
Abstract: The morphology of microcrystals has an important influence on optical property. In this work, new 3D self-assembled NdVO4 microcrystals with sphere and stick-shape morphology have been prepared by hydro-thermal method. Crystal growth mechanism has been studied. The morphology transformation of 3D self-assembled NdVO4 microcrystals is dependent on the reacting time of the precursor. The morphology of NdVO4 microcrystal changes as reacting time goes on. Moreover, energy level transition mechanism in NdVO4 microcrystal has been discussed. NdVO4 microcrystals realized near-infrared (NIR) emissions at 750, 808 and 853 nm under 980 nm laser. This study proved that NdVO4 microcrystals have good application prospects such as bio-imaging, photochemical catalysis and silicon-based solar cell.